The Gender Gap in Income and the COVID-19 Pandemic - Karina Doorley; Cathal O'Donoghue; Denisa Maria Sologon (Institute of Labor Economics (IZA), 2021)
The gender income gap is large and well documented for many countries. Recent research shows that it is mainly driven by differences in working patterns between men and women, but also by wage differences. The tax-benefit system cushions the gender income gap by redistributing between men and women. The Covid-19 pandemic has resulted in unprecedented levels of unemployment in 2020 in many countries, with some suggestion that men and women have been differently affected. This research investigates the effect of the Covid-19 pandemic on the gender gap in income in Ireland. Using nowcasting techniques and microsimulation, we model the effect of pandemic induced employment and wage changes on market and disposable income. We show how the pandemic and the associated tax-benefit support can be expected to change the income gap between men and women. Policy conclusions are drawn about future redistribution between men and women.
Keywords: D31; H23; J16; J31; 330; gender inequality; Ireland; tax-benefit system; COVID-19